Fertility-sparing management of gynecological cancers. Issue 2 (October 2015) - Fastrez, M; Houba, C; Vandromme, J; Rozenberg, S
Highlights The purpose of our review is to resume available evidence for the conservative management of gynecological cancers. Cone biopsy, simple or radical trachelectomy can be proposed as a fertility-sparing procedure to treat uterine cervical cancer. Hormone therapy can be used for the conservative management of early stage, well-differentiated endometrial cancer. Fertility-sparing therapeutic options for the management of the different histological types of ovarian cancer are also presented. Data regarding the selection of patients, surgical techniques, obstetrical issues and cancer prognosis are summarized. Fertility-sparing treatments of gynecological malignancies should be discussed in a multidisciplinary team and proposed to eligible patients who are younger than 40 and wish to preserve their fertility.